Synthesis of telechelic aliphatic cyclopolymers by controlled radical polymerization - Can, Aydın. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Powder coating is a growing industry which has many application areas for many surfaces. The coating mixture has many different ingredients. The highest percentage of a powder coating mixture in terms of both volume and weight is the resin which is a crosslinkable polymer with specific properties. Some of the important properties are processability, stability, reactivity. Beside these properties a powder coating resin has to have certain physical properties which affect the coating quality and manufacturing process. Among many, the most important one is a given Tg range. For example for a curing temperature of 140-150 0C the Tg of the resin has to be adjusted to 55-60 0C. Generally reaching these values is possible only using relatively high molecular weight aliphatic polyesters (10,000-20,000 g/mol). Having similar properties with low molecular weight aliphatic polymers has not been investigated previously. Aliphatic cyclopolymers derived from tert-butyl {460}-(hydroxymethyl)acrylate dimer(TBHMA) were synthesized via atom transfer radical polymerization (ATRP) to be used as potential base resins for powder coating applications. A variety of polymers were synthesized with various molecular weights and glass transition temperatures (Tg). To reach the desired Tg’s, two new di-initiators containing di- and tetra-ethylene glycol soft units were synthesized and used in the cyclopolymerization of tert-butyl a- (hydroxymethyl)acrylate (TBHMA). Polymerizations were carried out in xylene. Cu(I)Br/PMDETA was chosen as the active catalyst complex. It was found that molecular weights of polymers directly affected the Tg in the molecular weight range that was chosen. Using the new soft-block containing di-initiators, the Tg of the polymers were decreased to the desired scales (55-60 oC). Also low polydispersities and high conversions were achieved via ATRP. Two alternative studies were chosen for functionalization: pendant crosslinking and end functional crosslinking units. For pendant approach, glycidyl acrylate and methacrylate units tried to incorporate to the polymer system either directly as the monomer or indirectly to the macro monomer. By the help of living nature of ATRP, end group functionalization studies were done via using allyl alcohol and undeconoic acid under ATRP conditions. Characterization of all these cyclopolymers and copolymers were also investigated.
Keywords: Plastic powders.; Plastic coating.; Aliphatic compounds.; Cyclopolymerization.